Biologically optimized helium ion plans: calculation approach and its in vitro validation. (20th May 2016) - Mairani, A; Dokic, I; Magro, G; Tessonnier, T; Kamp, F; Carlson, D J; Ciocca, M; Cerutti, F; Sala, P R; Ferrari, A; Böhlen, T T; Jäkel, O; et al.
Abstract: Treatment planning studies on the biological effect of raster-scanned helium ion beams should be performed, together with their experimental verification, before their clinical application at the Heidelberg Ion Beam Therapy Center (HIT). For this purpose, we introduce a novel calculation approach based on integrating data-driven biological models in our Monte Carlo treatment planning (MCTP) tool. Dealing with a mixed radiation field, the biological effect of the primary 4 He ion beams, of the secondary 3 He and 4 He ( Z = 2) fragments and of the produced protons, deuterons and tritons ( Z = 1) has to be taken into account. A spread-out Bragg peak (SOBP) in water, representative of a clinically-relevant scenario, has been biologically optimized with the MCTP and then delivered at HIT. Predictions of cell survival and RBE for a tumor cell line, characterized by ( α / β ) p h = 5.4 Gy, have been successfully compared against measured clonogenic survival data. The mean absolute survival variation ( μ Δ S ) between model predictions and experimental data was 5.3% ± 0.9%. A sensitivity study, i.e. quantifying the variation of the estimations for the studied plan as a function of the applied phenomenological modelling approach, has been performed. The feasibility of a simpler biological modelling based on dose-averaged LET (linear energy transfer) has been tested. Moreover, comparisons with biophysical models such as the local effect model (LEM) and the repair-misrepair-fixation (RMF) model were performed. μ Δ S values for the LEM and the RMF model were, respectively, 4.5% ± 0.8% and 5.8% ± 1.1%. The satisfactorily agreement found in this work for the studied SOBP, representative of clinically-relevant scenario, suggests that the introduced approach could be applied for an accurate estimation of the biological effect for helium ion radiotherapy.